Meningkatkan Kemampuan Konsentrasi Belajar dan Keterampilan Berkomunikasi Menggunakan Model BANUA dan Permainan Ular Tangga Edukasi Dikelas III SDN Antasan Besar 7 - Norma Paulina; Zain Ahmad Fauzi; Herti Prastitasari; Fathul Jannah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
This study was motivated by the low level of concentration and communication skill of student, the lack of use interesting learning media, dand classroom conditions that tend to be boring, so that learning outcomes are not optimal. To overcome this, this research was conducted in the form of classroom action research for three cycle. The research participants consisted 0f 20 students of class III C SDN Antasan Besar 7 Banjarmasin. The date colected werw qualitative and obtained through observation of teacher activities. The results showed that the application of the BANUA Model and the Educational Snakes and Ladders Game was effective. Teacher and student activities increased, as well as the concentration ability, communication skills, and recommended that teachers continue to explore similar innovative learning models to increase student participation and achievement.